Thrombotic microangiopathy associated with bortezomib treatment in a patient with relapsed multiple myeloma - Urpu Salmenniemi; Kari Remes (Italy, 2022)
Thrombotic thrombocytopenic purpura (TTP) and hemolytic-uremic syndrome (HUS) describe microvascular occlusive disorders characterized by thrombocytopenia due to increased platelet aggregation and fragmentation hemolysis. We report here what to our knowledge is the second case of TTP/HUS associated with bortezomib treatment.